African Ancestry Is Associated with Asthma Risk in African Americans - Flores, Carlos; Ma, Shwu-Fan; Pino-Yanes, María; Wade, Michael S.; Pérez-Méndez, Lina; Kittles, Rick A.; Wang, Deli; Papaiahgari, Srinivas; Ford, Jean G.; Kumar, Rajesh; Garcia, Joe G. N. (PLOS ONE, 2012)
Background Asthma is a common complex condition with clear racial and ethnic differences in both prevalence and severity. Asthma consultation rates, mortality, and severe symptoms are greatly increased in African descent populations of developed countries. African ancestry has been associated with asthma, total serum IgE and lower pulmonary function in African-admixed populations. To replicate previous findings, here we aimed to examine whether African ancestry was associated with asthma susceptibility in African Americans. In addition, we examined for the first time whether African ancestry was associated with asthma exacerbations. Methodology/Principal Findings After filtering for self-reported ancestry and genotype data quality, samples from 1,117 self-reported African-American individuals from New York and Baltimore (394 cases, 481 controls), and Chicago (321 cases followed for asthma exacerbations) were analyzed. Genetic ancestry was estimated based on ancestry informative markers (AIMs) selected for being highly divergent among European and West African populations (95 AIMs for New York and Baltimore, and 66 independent AIMs for Chicago). Among case-control samples, the mean African ancestry was significantly higher in asthmatics than in non-asthmatics (82.0±14.0% vs. 77.8±18.1%, mean difference 4.2% [95% confidence interval (CI):2.0–6.4], p<0.0001). This association remained significant after adjusting for potential confounders (odds ratio: 4.55, 95% CI: 1.69–12.29, p = 0.003). African ancestry failed to show an association with asthma exacerbations (p = 0.965) using a model based on longitudinal data of the number of exacerbations followed over 1.5 years. Conclusions/Significance These data replicate previous findings indicating that African ancestry constitutes a risk factor for asthma and suggest that elevated asthma rates in African Americans can be partially attributed to African genetic ancestry.